The Music of Rene Drouard de Bousset (1703-1760): a Source Study and Stylistic Survey, with Emphasis on His Sacred Output : a thesis submitted to the New Zealand School of Music in fulfilment of the degree of Master of Music in Musiology - Smith, Felicity (New Zealand School of Music, 2008)
Rene Drouard de Bousset (1703-1760) was an admired composer and an organist of renown. This thesis examines this musician's life and work, and attempts to bring Bousset's music, hitherto largely unknown, to the attention of musicologists and performers today. Primarily a source study, the thesis makes a survey of all known copies of Bousset's published works, addressing questions of dates, reprints and corrections. Historical context and musical style are also discussed. Particular emphasis is given to Bousset's sacred music in the French language two volumes of sacred cantatas and eight settings of Odes sacrees by Jean-Baptiste Rousseau - and its place within the French tradition of Psalm paraphrase settings. The figure of J.B. Rousseau is also examined, as the librettist of Bousset's Odes, and as an important literary contributor to French music at the turn of the eighteenth century. The source study is supplemented by a catalogue in the style of the Philidor Oeuvres database produced by the Centre de Musique Baroque de Versailles, containing all Bousset's known works, extant and lost. This exposition of Bousset's compositional output is prefaced by a biographical overview assembled principally from eighteenth century publications and archival documents. Volume II of this thesis comprises a critical performing edition of Bousset's first volume of Cantates spirituelles (1739).
Keywords: Rene Drouard de Bousset (1703-1760); 18th century music; French music studies; French composers; French musicians; Musical criticism; Fields of Research::410000 The Arts::410100 Performing Arts Studies::410101 Music studies